Mathematical Analysis of The Hash Functions as a Cryptographic Tools for Blockchain - Gençoğlu, Muharrem Tuncay (My University, 2022)
Blockchain is one of the most interestingly developing technologies today, with its applications in many fields from smart contracts to cryptocurrencies. In this respect, blockchain is a hot modern topic nowadays. This study presents a mathematical analysis of cryptographic hash functions, which are one of the most important elements for understanding the security foundations of this technology. In this analysis presented; Hash functions, which are one of the building blocks of blockchain technology, used to ensure information integrity, have proven to be resistant to collision resistance, which is very important in data mining. Thus, a theory has been put forward that will contribute to time and energy saving, which is one of the important problems in data mining, in which blockchain technology is used.
Keywords: Blockchain; mathematical analysis; hash functions; cryptographic hash functions; hash functions; blockchain; cryptographic hash functions; mathematical analysis